P113: Presentations for hypoglycemia associated with diabetes mellitus to emergency departments in a Canadian province: a database and cost analysis. (2nd June 2016) - Alexiu, C.; Jelinski, S.; Chuck, A.; Rowe, B.H.
Abstract : Introduction: Diabetes mellitus (DM) is a common chronic disease. The Canadian Diabetes Association (CDA) estimated that the national direct cost of DM accounts for approximately 3.5% of public healthcare spending. The economic burden has been estimated to be 12.2 billion in 2010 and projected to increase by 4.7 billion (38%) by 2020. For the province of Alberta, the estimated cost was 1.3 billion in 2015 and 1.7 billion for 2025. The cost of lesser complications of DM like hypoglycemia is not as well understood. The objective of this study was to estimate the health system cost of presentations by adults to Alberta emergency departments (ED) for hypoglycemia associated with type 1 (T1DM) or type 2 (T2DM) diabetes.Methods: A retrospective cohort study was conducted using administrative data for Alberta for a five-year period (fiscal years 2010/11-2014/15). Data were sourced from an administrative database: National Ambulatory Care Reporting System (NACRS). Records of interest were those for ED patients with an ICD-10-CA diagnosis of DM-associated hypoglycemia. A top-down approach was used to estimate costs, excluding physician and ambulance fees. This involved resource intensity weight (RIW), cost of a standard hospital stay (CSHS), and adjustment for inflation (to average value of Canadian dollar for Alberta for January-September 2015). A descriptive analysis was conducted.Results: Data extraction yielded 7, 835 presentations by 5, 884 patients. The median RIW was 0.0547. RIWs are centered at 1, thus the resource-use/cost of these presentations is well below that of the "average" case. Estimated costs per episode ranged from 108.63 to 4, 136.59 with median of 431.11 (IQR: 369.40-639.50). Median episodic subgrouped costs were as follows: sex: 427.72 for males, 439.20 for females; DM type: 411.61 for T1DM, 511.63 for T2DM; date period: 835, 862.09/year, 69, 655.17/month, 16, 030.23/week, and 2, 288.78/day.Conclusion: Using population-based administrative data, we identified median costs for DM-associated hypoglycemia of approximately 430/case. Given the frequency, this condition incurs significant healthcare resource use and costs; continued efforts to reduce these ED visits seem worthwhile.